New advances in the development of a vaccine against paracoccidioidomycosis - Travassos, Luiz R R.; Taborda, Carlos P. (Frontiers in Microbiology, 2012)
Paracoccidioidomycosis (PCM) is an endemic Latin American mycosis caused by Paracoccidioides brasiliensis and also by the recently described P. lutzii. The systemic mycosis is the 10th leading cause of death due to infectious diseases in Brazil. As published, 1,853 patients died of PCM in the 1996–2006 decade in this country. The main diagnostic antigen of P.brasiliensis is the 43 kDa glycoprotein gp43, and its 15-mer peptide QTLIAIHTLAIRYAN, known as P10, contains the T-CD4+ epitope that elicits an IFN-γ-mediated Th1 immune response, which effectively treats mice intratracheally infected with PCM. The association of peptide P10 with antifungal drugs rendered an additive protective effect, even in immunosuppressed animals, being the basis of a recommended treatment protocol. Other immunotherapeutic tools include a peptide carrying a B cell epitope as well as protective anti-gp43 monoclonal antibodies. New delivery systems and gene therapy have been studied in prophylactic and therapeutic protocols to improve the efficacy of the recognized antigens aiming at a future vaccine as co-adjuvant therapy in patients with PCM.